KOLABORASI EKONOMI DALAM UPAYA MENGGERAKKAN RODA PEREKONOMIAN UMKM INDONESIA MELALUI STARTUP BUKUWARUNG - Pangestu, Nungky Satrina; Harmonis, Harmonis (Cahaya Ilmu Bangsa, 2024)
The role of financial technology (fintech) startups in empowering Micro, Small, and Medium Enterprises (MSMEs) has proven to be significant, particularly in financial management and digital technology adoption. This paper explores the contributions of fintech in enhancing the efficiency, accessibility, and growth of MSMEs. Fintech startups provide innovative solutions to address the challenges faced by MSMEs, including improved financial management, broader access to financial services, and support for financial inclusion. The focus of this paper is on the startup BukuWarung and its role in advancing the financial digitalization of MSMEs through its application. BukuWarung not only offers financial management tools but also facilitates business-to-business collaboration and crucial economic negotiations, such as pricing, contracts, partnerships, and financing. Effective negotiations in the integration of fintech technology ensure implementation that benefits all involved parties, including MSMEs, fintech providers, and other stakeholders. Through its innovation and services, BukuWarung helps MSMEs tackle various challenges, enhance their competitiveness, and achieve sustainable growth.Keywords: Fintech Startup, MSMEs, Economic Negotiation, Financial Digitalization, Business-to-Business Collaboration Peran startup financial technology (fintech) dalam pemberdayaan Usaha Mikro, Kecil, dan Menengah (UMKM) telah terbukti signifikan, terutama dalam hal pengelolaan keuangan dan adopsi teknologi digital. Makalah ini mengeksplorasi kontribusi fintech dalam meningkatkan efisiensi, aksesibilitas, dan pertumbuhan UMKM. Startup fintech menawarkan solusi inovatif untuk mengatasi tantangan yang dihadapi UMKM, termasuk pengelolaan keuangan yang lebih baik, akses yang lebih luas ke layanan keuangan, dan dukungan untuk inklusi keuangan. Fokus makalah ini adalah pada startup BukuWarung dan perannya dalam meningkatkan digitalisasi keuangan UMKM melalui aplikasi mereka. BukuWarung tidak hanya menyediakan alat pengelolaan keuangan, tetapi juga memfasilitasi kolaborasi business-to-business dan negosiasi ekonomi yang penting, seperti harga, kontrak, kemitraan, dan pembiayaan. Negosiasi yang efektif dalam integrasi teknologi fintech memastikan implementasi yang menguntungkan semua pihak terkait, termasuk UMKM, penyedia fintech, dan pemangku kepentingan lainnya. Dengan inovasi dan layanan yang ditawarkan, BukuWarung membantu UMKM menghadapi berbagai tantangan, memperbaiki daya saing mereka, dan mencapai pertumbuhan berkelanjutan.Kata Kunci: Startup Fintech, UMKM, Negosiasi Ekonomi, Digitalisasi Keuangan, Kolaborasi Business-to-Business